2008
DOI: 10.1111/j.1399-3038.2007.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Children with absent surfactant protein D in bronchoalveolar lavage have more frequently pneumonia

Abstract: Surfactant protein D (SP-D) is an important component of the pulmonary host defense system. We hypothesized that bronchoalveolar lavage (BAL) SP-D levels are lower in children presenting with recurrent bronchitis, providing evidence for a role of SP-D in human respiratory diseases. SP-D levels in BAL were measured in 45 children, who suffered from recurrent bronchitis for an average of 2-3 yr. Clinical outcome was assessed 2 yr after BAL. For comparison, BAL fluids from 15 control children without respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
(57 reference statements)
0
16
0
1
Order By: Relevance
“…Children with severe RSV infection or recurrent pneumonias may have decreased or absent levels of SP-D in BAL fl uid during the acute phase of the infection, such that the role of NKX2-1 in SP-D gene expression is less clear. 27,28 Murine SP-D gene expression, as assessed by microarray, was actually increased in transgenic mice expressing a phosphorylation mutant form of Nkx2-1 , suggesting negative regulation by TTF-1; however, no changes in human SP-D gene expression were detected with either gain or loss of function approaches in vitro. 19,29 Thus, it is diffi cult to determine the relationship between the NKX2-1 mutations, SP-D expression, and the recurrent infections in these children, especially in light of other children in this report with NKX2-1 mutations and recurrent infections but who do not have evidence of decreased SP-D expression.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Children with severe RSV infection or recurrent pneumonias may have decreased or absent levels of SP-D in BAL fl uid during the acute phase of the infection, such that the role of NKX2-1 in SP-D gene expression is less clear. 27,28 Murine SP-D gene expression, as assessed by microarray, was actually increased in transgenic mice expressing a phosphorylation mutant form of Nkx2-1 , suggesting negative regulation by TTF-1; however, no changes in human SP-D gene expression were detected with either gain or loss of function approaches in vitro. 19,29 Thus, it is diffi cult to determine the relationship between the NKX2-1 mutations, SP-D expression, and the recurrent infections in these children, especially in light of other children in this report with NKX2-1 mutations and recurrent infections but who do not have evidence of decreased SP-D expression.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Low levels of pulmonary surfactant proteins are associated with increased risk of pneumonia [Griese et al 2008]. A polymorphism in surfactant protein B, SP-B ĂŸ1580 (T/C) was associated with increased risk of pneumonia in one cohort study [Quasney et al 2004], but no further studies have been reported.…”
Section: Pattern Recognition Moleculesmentioning
confidence: 98%
“…In human patients, SP-D inhibited the chemotaxis of eosinophils suggesting an anti-inflammatory role in the lungs of asthmatic subjects (82). Children with decreased or absent SP-D in bronchoalveolar lavage fluid were found to have more frequent respiratory diseases (83). Most of the data seem to suggest that both human and murine SP-A/D seem to play a role in controlling allergy and airway inflammation.…”
Section: Acute/early Phase Responsementioning
confidence: 99%